The Importance of Intergenerational Cooperation for the Elderly in the Third and Fourth Ages (Journal of Universal Excellence, 2026)
Research question: Is intergenerational cooperation important for the elderly?Purpose: The purpose of the research was to establish the importance of intergenerational cooperation for the elderly in the third and fourth ages in homes for the elderly.Methods: A desk and field research was used. In addition to the literature study, statistical data of the Statistical Office of the Republic of Slovenia were analysed. A field research in Slovenian homes for the elderly was conducted to obtain the positions. Randomly chosen elderly were included. Interviewing was performed as a method of data acquisition and SPSS 20 was used for data processing. 390 older people residing in the homes for the elderly in Pomurje participated in the research conducted in 2017.Summary of results: We found that when asked about intergenerational socialising, the elderly often emphasised how much they look forward to each new visit of children from kindergartens or elementary schools and young secondary school students who come to some elderly weekly as a part of a compulsory elective course, and enrich their days of residing in a home for the elderly with a cultural programme or direct socialising (conversation, board games).Impact on society: In our opinion this kind of research significantly influences development of intergenerational cooperation as an integral part of multi-generational coexistence in Slovenia and in societies in general.Impact on organisation: The findings of the research are relevant to the homes for the elderly and other forms of care beyond institutional care. Thus, they can connect in intergenerational cooperation and optimise work.Originality: Study on intergenerational cooperation is one of several studies of this kind in Slovenia.Limitations of research: Obstacles met by the elderly in institutional as well as noninstitutional care (myopia and hearing impairment which made interviewing difficult).
Keywords: ageing; old age; leisure activities; intergenerational cooperation; the elderly